2021
DOI: 10.1002/ps.6581
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive picture of foraging strategies ofNeoseiulus cucumerisandAmblyseius swirskiion western flower thrips

Abstract: BACKGROUND: This study evaluated the potential of Neoseiulus cucumeris Oudemans and Amblyseius swirskii Athias-Henriot (Acari: Phytoseiidae) for controlling western flower thrips (WFT), Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), by determining the functional response, numerical response, prey switching and mutual interference behaviors of the predators.RESULTS: A type II functional response was detected for two predator species fed on WFT first instars. The attack rate was higher for A. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The highest predation was observed in the control treatment where A. swirskii and N. californicus consumed the highest number of S. dorsalis pupae. Amblyseius swirskii is a known predator of various thrips species (Wimmer et al 2008;Dalir et al 2021;Schoeller et al 2022) and has been demonstrated to efficiently suppress S. dorsalis on strawberries in a greenhouse (Lahiri and Yambisa 2021). Similar to A. swirskii, N. californicus is a generalist predator that can survive feeding on thrips (Walzer et al 2004;Rahmani et al 2009;Azadeh et al 2013) but exhibits preference for spider mites (McMurtry et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The highest predation was observed in the control treatment where A. swirskii and N. californicus consumed the highest number of S. dorsalis pupae. Amblyseius swirskii is a known predator of various thrips species (Wimmer et al 2008;Dalir et al 2021;Schoeller et al 2022) and has been demonstrated to efficiently suppress S. dorsalis on strawberries in a greenhouse (Lahiri and Yambisa 2021). Similar to A. swirskii, N. californicus is a generalist predator that can survive feeding on thrips (Walzer et al 2004;Rahmani et al 2009;Azadeh et al 2013) but exhibits preference for spider mites (McMurtry et al 2013).…”
Section: Discussionmentioning
confidence: 99%